2022
DOI: 10.3390/su142013249
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Policy’s Effect on Cross-Border Mergers’ Decisions—Theoretical and Empirical Analysis

Abstract: To explore the relationship between industrial policy and cross-border M&As in Chinese enterprises, the PSM method and a two-way fixed model were used. Using a sample of A-share listed companies during the period 2005–2019, we theoretically and empirically analyzed the mediating role of financial constraints and the moderating role of political connections between the companies. It was found that industrial policy has a significant positive effect on cross-border M&As and that firms’ financial constrai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 71 publications
0
2
0
Order By: Relevance
“…Using regional data covering the years 2010 to 2022, the research undertaken in this paper explores the dynamics of the Indonesian economy by empirically assessing the consequences of structural change on industrial Policy. Chen (2022) shows that by improving the analysis and estimating accuracy, the two-way fixed effects model can handle the panel data's heteroskedasticity and autocorrelation issues while controlling for individual and time-fixed effects. Chen (2022) and Xu et al (2022) drew a model as shown in Equation (1).…”
Section: Model Settingmentioning
confidence: 99%
“…Using regional data covering the years 2010 to 2022, the research undertaken in this paper explores the dynamics of the Indonesian economy by empirically assessing the consequences of structural change on industrial Policy. Chen (2022) shows that by improving the analysis and estimating accuracy, the two-way fixed effects model can handle the panel data's heteroskedasticity and autocorrelation issues while controlling for individual and time-fixed effects. Chen (2022) and Xu et al (2022) drew a model as shown in Equation (1).…”
Section: Model Settingmentioning
confidence: 99%
“…International acquisitions which the essence is to increase corporate profits are the combination of two or two more enterprises [2]. The acquiring company controls the financial and operational aspects of the acquired company [3].…”
Section: Introductionmentioning
confidence: 99%